2012
DOI: 10.1159/000334621
|View full text |Cite
|
Sign up to set email alerts
|

Potential Preventive Effects of a New Visual Intervention for Accommodative Insufficiency and Asthenopia due to Sustained Near Task

Abstract: Background: The objective of this study was to experimentally investigate whether a new visual intervention with optical and binocular vergence demands prevents accommodative insufficiency and asthenopia after sustained periods of visual task. Methods: Fourteen female students were given the intervention with optical and binocular vergence demands for 1.5 min immediately after 20 min of a sustained task on a three-dimensional display. Before and after the trial, their ocular functions were measured and their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…Given the relationship between both systems, visual and cervical, it would be an option in future research to propose an intervention through a visual therapy program in subjects with accommodative dysfunctions and neck pain because visual therapy has proven to be a useful treatment option in subjects with accommodative anomalies, and assess whether there are changes in possible neck dysfunctions. Regarding the limitations of our study, it is important to emphasize the small sample size, which should make us carefully consider the results presented.…”
Section: Discussionmentioning
confidence: 99%
“…Given the relationship between both systems, visual and cervical, it would be an option in future research to propose an intervention through a visual therapy program in subjects with accommodative dysfunctions and neck pain because visual therapy has proven to be a useful treatment option in subjects with accommodative anomalies, and assess whether there are changes in possible neck dysfunctions. Regarding the limitations of our study, it is important to emphasize the small sample size, which should make us carefully consider the results presented.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown high correlations between asthenopic symptoms and AI. 9 , 12 , 34 A Swedish school children-based study examining 216 children of grades 1–8 reported asthenopic symptoms among 23.1%, of which 11.1% had abnormal near point of accommodation. Earlier studies in children with lower accommodative amplitudes showed that the subjects had severe difficulty reading near text for long hours, diplopia and severe asthenopic symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…2,3 Systemic, neurological, and local ocular pathologies can cause accommodative insufficiency. Head trauma, Parkinson disease, multiple sclerosis, encephalopathies, meningitis, midbrain pathology, subdural haematoma, pharmacological and toxic agents, viral infections, diabetes, botulism, diphtheria, and oculomotor nerve palsy are among causes of accommodation insufficiency.…”
Section: Discussionmentioning
confidence: 99%